Habitual generation of filter bubbles - Kaluža, Jernej (Javnost (Ljubljana), 2021)
In the last decade, digital filter bubbles have become widely discussed phenomena in different fields within the broader discipline of media and communication studies. This paper focuses on the question of why they are problematic for the functioning of the public sphere. This paper argues that algorithmic personalisation can lead to the fragmentation, polarisation, and radicalisation of the public sphere because of the complex relationship between human agency and technology that mutually encourage one another through habitual adaptation. Through the concept of habit, such theoretical grounding enables a critique of existing empirical research regarding the filter bubble effect, with the argument that the main problem is not information isolation or the reduced accessibility/visibility of selected content, but the habitual adaptation of content to individual users, which can explain why users stick to certain content. The article concludes with the finding that the problem of algorithmic personalisation should be studied as a broader historic phenomenon indicative of the decline of the public sphere, which is itself caused by the conflict between public and commercial interests.
Keywords: Algorithms; Algoritmi; filter bubble; Habit; Javna sfera; Navada; personalisation; Public sphere; radicalisation